Plant growth acceleration using a transparent Eu3+-painted UV-to-red conversion film - Sunao Shoji; Hideyuki Saito; Yutaka Jitsuyama; Kotono Tomita; Qiang Haoyang; Yukiho Sakurai; Yuhei Okazaki; Kota Aikawa; Yuki Konishi; Kensei Sasaki; Koji Fushimi; Yuichi Kitagawa; et al. (Scientific Reports, 2022)
Abstract The stimulation of photosynthesis is a strategy for achieving sustainable plant production. Red light is useful for plant growth because it is absorbed by chlorophyll pigments, which initiate natural photosynthetic processes. Ultraviolet (UV)-to-red wavelength-converting materials are promising candidates for eco-friendly plant cultures that do not require electric power. In this study, transparent films equipped with a UV-to-red wavelength-converting luminophore, the Eu3+ complex, were prepared on commercially available plastic films for plant growth experiments. The present Eu3+-based films absorb UV light and exhibit strong red luminescence under sunlight. Eu3+-painted films provide significant growth acceleration with size increment and biomass production for vegetal crops and trees in a northern region. The plants cultured with Eu3+-painted films had a 1.2-fold height and 1.4-fold total body biomass than those cultures without the Eu3+ luminophores. The present film can promote the plant production in fields of agriculture and forestry.